A novel porphyrin dye with phenoxazine as donor unit for efficient dye-sensitized solar cells. (June 2021) - Li, Shengzhong; Zhang, Shuangyu; Mei, Shu; Kong, Xiangfei; Yang, Miao; Wu, Wenjun; Zhang, Shuhua; Tan, Haijun
Abstract: A novel porphyrin dye T-2 with phenoxazine (POZ) as donor unit has been synthesized and utilized for dye-sensitized solar cells (DSSC). Compare with porphyrin dye T-1 (in which triphenylamine as a donor unit), the DSSC based on T-2 exhibited a significantly higher J sc (16.35 mA cm −2 ) and V oc (670 mV) than that of T-1 (9.13 mA cm −2, 610 mV), which attribute to the higher IPCE and τ of the device based on T-2 . Correspondingly, the T-2-based device achieved a photoelectric conversion efficiency (PCE) of 7.64% (N719, 8.45%). By detailed investigation of the relationship between structure and performance, we found the butterfly-shaped structure, stronger electron-donating capability, and the extra alkyl chain of POZ are the main reasons leading to better performance of T-2 than that of T-1 in the DSSC device. Graphical abstract: Image 1 Highlights: A novel porphyrin dye T-2 with phenoxazine (POZ) as donor unit has been synthesized and utilized for DSSC. A higher efficiency of 7.64% (N719 = 8.45%) has been achieved. POZ is a very promising donor unit for developing high-efficiency porphyrin dyes for DSSC.